Peregrinação a Santiago de Compostela com os olhos do presente - Panazzolo, Flávia de Brito (2021)
This thesis approaches the theme of pilgrimage in the current days on the Camino to Santiago to Compostela, Spain. The study succinctly presentes the history of the Way, my ethnographic reporto the experience of the pilgrimage and, through an anthopological perspective, the relationships existing in the market of services offered in communication, food, accomodation, transport, travel agencies and the various giffts and souvenirs shops. The objective of the work is to undestand what is happening in the current world, more precisely, in pilgrimages, analyzing through the ethnographic method the pilgrimage along the Portuguese route on the Camino to Santiago to Compostela, which has become a consolidated tourist attraction, with a large consumption in the cultural, social and economic scope, in addition to bringing a reflection on the body, on the experiences of pain, fatigue, limits, anguish and overcoming in the space of sacrifices due to the sacred and faith, motivations and post-path reflections. I seek to verify how the pilgrimage to Compostela has changed the life and outlook os these pilgims through bodily overcoming. Have bodily problems, such as muscle pain, foot pain, among others, helped pilgrims in their spiritual Evolution? I presente how these pilgrims narrate their motivations, their personal sacrifices during the journey and what were their learning and evaluations after the journey.